Valorisation potential of black tea processing wastes for bioactive compounds recovery and renewable energy production - Ünyay, Hilal; Altay, Hatice Özmen; Perendeci, N. Altınay; Szufa, Szymon; Özdemir, Feramuz; Angelidaki, İrini (Elsevier, 2025)
Tea processing wastes, rich in carbohydrates—primarily cellulose and hemicellulose—and bioactive compounds such as polyphenols and caffeine, represent a valuable biomass resource that can be utilised for antioxidant extraction and energy recovery. Tea factories are assumed to produce uniform waste due to blending and accumulating residues in shared storage; however, four distinct waste types arise at different processing stages, each showcasing unique traits. Waste samples were taken directly from two different factories that produce black tea with Çaykur (nonpressed orthodox + rotorvane + pressed orthodox) and Rotorvane + CTC production methods belonging to the Turkish Tea Board, Türkiye, within three shooting periods and four black tea processing stages. Tea processing waste samples were evaluated from the point of resource recovery as bioactive compounds and energy production. Significant variations were found in total phenolic content (4.75–8.65 gGAE/100 gDM), gallic acid (0.47–0.61 %), and caffeine (1.33–2.54 %) levels among the tea wastes examined. Tea processing waste from the Çaykur method exhibited higher caffeine content. Methane production from anaerobic digestion ranged from 97.3 to 203.9 mLCH4/gVS. Under torrefaction at 285°C, the higher heating value (HHV) demonstrated a remarkable 43.9 % increase, reaching a peak HHV of 24.36 MJ/kg. Torrefaction yielded impressive energy yields of 82.3 % and 92.1 %. These findings underscore the efficacy of torrefaction at this temperature in boosting the energy content of the biomass while maintaining high energy yield percentages. This study presents the first integrative and multidimensional framework for tea waste valorisation, offering comprehensive insights into its dual-purpose utilisation by concurrently assessing bioactive compounds such as total phenolic content, polyphenolic profile, and caffeine concentration and energy potential through biogas and biochar production across different tea manufacturing techniques, waste stream types, and shooting period.
Appendix A. Supplementary material: https://ars.els-cdn.com/content/image/1-s2.0-S2213343725018202-mmc1.docx
This study is based on the master's thesis (MSc.) for the H. O., Akdeniz University, Türkiye. This work was completed while the first author was a Doctoral Candidate at the Interdisciplinary Doctoral School at the Lodz University of Technology, Poland.
Keywords: anaerobic digestion; bioactive compounds; biochar; biogas; black tea production methods; tea processing waste; resource recovery; torrefaction